Analysis of Metallic-to-Oxide Sputtering Mode Transition During Reactive Magnetron Deposition of Aluminum Oxide Coatings - Andrey V. Kaziev; Alexander V. Tumarkin; Dobrynya V. Kolodko; Maksim M. Kharkov; Raghavendra Konaguru; Dmitry G. Ageychenkov; Nikolay N. Samotaev; Konstantin Yu. Oblov (Applied Sciences)
Direct current (DC) reactive magnetron discharge in Ar + O2 mixtures with an aluminum (Al) target was investigated. Electrical measurements of the discharge voltage and current along with the deposition rate trends observed with varying the oxygen flow rate indicated the presence of hysteresis, typical to when using a DC power supply. The transition between metallic and oxide (compound) modes was analyzed in more detail by measuring the mass-resolved fluxes of positively and negatively charged ions together with the optical emission spectra of plasma. The dependence of constituent ion fluxes (Ar+, Ar2+, Al+, O+, O2+, O−, and O2−) on the reactive oxygen gas flow rate was revealed, indicating the transition (in 1.2–1.8 sccm O2 flow range) from a metallic regime to a poisoned regime. The optical diagnostics indicated a nonlinear hysteresis loop pattern of dependence for various constituents (ions and neutrals) of the magnetron discharge plasma. The comparison between the particle and optical measurements, though exhibiting a pronounced correlation, demonstrated individual features of both methods, which need to be taken into account when interpreting the results. The hysteresis patterns were further discussed by comparing the experimental data with the calculation results from the Berg model. An approach of adapting the model results to the case of a power-regulated magnetron power supply is expressed.